Equatorial ionospheric electrodynamic perturbations during Southern Hemisphere stratospheric warming events - Olson, M. E. (2013)
We use ground-based and satellite measurements to examine, for the first time, the characteristics of equatorial electrodynamic perturbations measured during the 2002 major and 2010 minor Southern Hemisphere sudden stratospheric warming (SSW) events. Our data suggest the occurrence of enhanced quasi-two fluctuations during the 2002 early autumnal equinoctial warming. They also show a moderately large multi-day perturbation pattern, resembling those during arctic SSW events, during 2002 late equinox, as the major SSW was weakening. We also compare these data with extensive recent results that showed the fundamentally important role of lunar semidiurnal tidal effects on low latitude electrodynamic perturbations during of arctic SSW events.